2012
DOI: 10.1111/j.1439-037x.2011.00502.x
|View full text |Cite
|
Sign up to set email alerts
|

Carbohydrate Dynamics in Leaves of Rapeseed (Brassica napus) Under Drought

Abstract: Until now, the carbohydrate dynamics in leaves of rapeseed under drought have largely been unknown. For this reason, a growth chamber study was conducted to examine whether the accumulation of carbohydrates under drought stress contributes to osmotic adjustment in leaf tissue. Plants of the cultivar Titan were subjected to temporary drought in the vegetative and reproductive stages. A third variant of long-term drought covered the period from leaf development to flowering. The level of sucrose decreased under … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(13 citation statements)
references
References 38 publications
0
13
0
Order By: Relevance
“…As far as the salt-tolerant cultivar Exagone is concerned, our data demonstrates that salinity indeed significantly increased the endogenous trehalose content in the leaves. Müller et al [66] recently reported such an increase in response to drought in rapeseed cultivar Titan. Since salt stress clearly presents an osmotic component compromising the plant water status [8,9], the reported increase in response to salt may be at least partly due to salt-induced modification in the plant water potential.…”
Section: Discussionmentioning
confidence: 99%
“…As far as the salt-tolerant cultivar Exagone is concerned, our data demonstrates that salinity indeed significantly increased the endogenous trehalose content in the leaves. Müller et al [66] recently reported such an increase in response to drought in rapeseed cultivar Titan. Since salt stress clearly presents an osmotic component compromising the plant water status [8,9], the reported increase in response to salt may be at least partly due to salt-induced modification in the plant water potential.…”
Section: Discussionmentioning
confidence: 99%
“…These compounds are osmoprotectant for cell protection from the harmful effects of stress. Muller et al (2012) showed the level of sucrose decreased under moderate water deficit, but concentrations of glucose, fructose, and trehalose were significantly enhanced and that of raffinose decreased in all variants of drought. 3.5.…”
Section: Total Soluble Sugar and Carbohydratesmentioning
confidence: 92%
“…Therefore, there is a need to identify alternative crops that have lower ET requirements than traditional crops and are well adapted to the region. Canola regulates carbohydrate dynamics and accumulates various metabolites including proline in drought to enhance its drought stress tolerance (Ma et al, 2004;Din et al, 2011;Müller et al, 2012). Therefore, understanding the critical growth stage of alternative crop for irrigation will help in developing proper irrigation strategies to maximize return per unit of water (Singh et al, 2016b).…”
Section: Growth-stage-based Irrigation Management On Biomass Yield mentioning
confidence: 99%
“…It reduces stomatal conductance and promotes stomatal closure to preserve plant hydration on reduction in leaf water status ( Johnston et al, 2002;Shafiq et al, 2014). Canola regulates carbohydrate dynamics and accumulates various metabolites including proline in drought to enhance its drought stress tolerance (Ma et al, 2004;Din et al, 2011;Müller et al, 2012). Therefore, canola could be a good alternative crop for the region.…”
Section: Growth-stage-based Irrigation Management On Biomass Yield mentioning
confidence: 99%